The effectiveness of developing instructional materials designed for vocabulary acquisition among visually impaired students using the Braille method - Saat, Abdus; Hasanah, Mamluatul; Faisol, Faisol; Haidar, Ali (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The urgency to develop Arabic vocabulary learning materials in Braille for visually impaired beginner students arises as a response to the persistent inequality of access to education within Islamic boarding schools (pesantren). The scarcity of specialized instructional media tailored to the characteristics of visual disabilities has hindered vocabulary acquisition, a crucial element in building reading skills and Arabic text comprehension. In this context, the development of Braille-based learning materials through a systematic instructional design approach—specifically the ADDIE model—offers a practical and inclusive educational solution.This study adopts a Research and Development (RD) methodology, utilizing the ADDIE framework, which comprises five stages: Analysis, Design, Development, Implementation, and Evaluation. The analysis phase involved field observations, in-depth interviews, and document reviews to assess the actual learning needs of visually impaired students at Pondok Pesantren Nurul Qur’an in Probolinggo. Based on this analysis, thematic vocabulary materials were designed around students’ daily environments, such as body parts, school facilities, daily activities, and food. The content was produced in Arabic Braille and enriched with interactive exercises, including letter arrangement, word matching, multiple-choice questions, and progressive reading and memorization tasks.The materials were validated by experts in Arabic language education, Braille methodology, and inclusive education. The results confirmed high pedagogical and technical feasibility. A limited trial with four students showed significant improvement in Braille reading skills, vocabulary comprehension, and self-confidence in independent learning. This innovation affirms the right to equitable and dignified education for students with disabilities and promotes inclusive pedagogical practices within Islamic educational institutions.